Efektivitas Pengeringan Pada Kolektor Surya Dengan Sudut Kemiringan 130 Menggunakan Bahan Absorber - Putra, Mhd Irwansyah; Syuhada, Ahmad; Nasution, Arya Rudi (Rekayasa Material, Manufaktur dan Energi, 2022)
Indonesia is an area with a fairly high intensity of sunlight because of its position on the equator. Its solar energy potential reaches 207.9 GW, while its use is only about 78.5 MW. Therefore, many studies have been conducted on the application of solar thermal energy which is a renewable energy source. One application of solar energy is used for the drying process of a material. In general, people in Indonesia still use traditional drying systems because solar energy is obtained free of charge and does not run out, so traditional drying is relatively cheap. The purpose of this study is to achieve the highest collector temperature by using heat absorption material on the absorber used in the solar collector with several variations of the absorber so as to optimize the heat temperature of the solar collector. This study tested the type of absorber of the most optimal heat absorption material on a solar collector with a slope angle of 1300 and 4 absorber variations, namely (1) iron sand and gram iron, (2) iron sand, (3) hot mix asphalt, and (4) asphalt and iron sand. This research was carried out by describing the tools designed with the preparation of measuring instruments, data collection and data processing carried out on the front page of the Faculty of Engineering and the Laboratory of Thermal Engineering, Faculty of Engineering, Syiah Kuala University. The tools used for the four flat plate solar collectors with the equipment and materials used in this study were wood (boards and beams) as a frame, mica plastic as a collector cover, iron sand and iron gram absorber material, iron sand, hot mix asphalt, asphalt. and iron sand, and rubber wood lat as insulation. The results showed that the distribution of air temperature along the channel tends to increase very sharply, especially in the bend area, this is due to sharp turns which result in flow turbulence. Thus, the highest temperature obtained for each absorber variation of sand and gram iron, iron sand, hot mix asphalt, and asphalt and iron sand with temperatures of 860C, 810C, 830C, and 840C. In this study, the intensity of sunlight is only 857.12 W/m2.